2021
DOI: 10.1371/journal.pone.0248813
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of SARS-COV-2 positivity in 516 German intensive care and emergency physicians studied by seroprevalence of antibodies National Covid Survey Germany (NAT-COV-SURV)

Abstract: Healthcare personnel are at risk to aquire the corona virus disease 2019 (COVID-19) caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). We evaluated the prevalence of SARS-CoV-2 antibodies and positive nasopharyngeal reverse transcriptase polymerase-chain reaction (RT-PCR) tests in German intensive care and emergency physicians. Physicians attending intensive care and emergency medicine training courses between June 16th and July 2nd 2020 answered a questionnaire and were screened for S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…Looking at the risk to acquire the SARS-CoV-2 infection privately or at work, we may assume that the participating hospitals were probably no places of infectious spread to employees in the first pandemic wave. Some studies on HCWs in Germany also differentiated between seroprevalence rates according to the risk at work [14,21], and investigated highrisk group HCWs on ICU, the COVID-19 ward and emergency department [19,22,23,31]. All these studies found a low seroprevalence up to 4.36% [18] in the first pandemic wave.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Looking at the risk to acquire the SARS-CoV-2 infection privately or at work, we may assume that the participating hospitals were probably no places of infectious spread to employees in the first pandemic wave. Some studies on HCWs in Germany also differentiated between seroprevalence rates according to the risk at work [14,21], and investigated highrisk group HCWs on ICU, the COVID-19 ward and emergency department [19,22,23,31]. All these studies found a low seroprevalence up to 4.36% [18] in the first pandemic wave.…”
Section: Discussionmentioning
confidence: 99%
“…Data from German HCWs are available from a variety of hospitals, but nearly all published data focus on the first pandemic wave [14][15][16][17][18][19][20] (Table 1). Two hospitals reported data until December 2020 [21,22], but no information for HCWs in Germany is available for the year 2021 so far. Employees of three hospitals of a secondary care hospital network and an associated fire brigade [39], actual data…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of infection control measures such as wearing PPE in daily practice might also allow HCWs to contain the spread of COVID 19 infection [ 48 , 49 ] through exclusive use of FFP2/FFP3 ( P = 0.99) and eye-protective devices ( P = 0.99) [ 50 ]. Similarly, Hou and colleagues proposed a level system of PPE protection for HCWs [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Table S4. Baseline characteristics of the studies excluded from the meta-analysis that assessed the association between influenza vaccination and SARS-CoV-2 infection or its outcome [ 30 , 36 , 69 , 70 , 87 , 88 , 89 , 90 , 91 , 92 , 93 , 94 , 95 , 96 , 97 , 98 , 99 , 100 ].…”
mentioning
confidence: 99%